Hydrating serum made of potassium azeloyl diglycinate with CMC-Na variations as a gelling agent on physical-chemical and safety tests - Rohmani, Sholichah; Aditya, Shafira Nur; Husna, Hanna Miftahul; Ermawati, Dian Eka; Utami, Diyah Tri (Faculty of Pharmacy, Universitas Pancasila, 2024)
Potassium azeloyl diglycinate is an ingredient for moisturizing the skin. In this research, potassium-azeloyl-diglycinate was formulated into a gel-based hydrating serum. A good serum gel can be identified by its physicochemical properties and stability, which are determined by the composition of the ingredients used, one of which is CMC-Na, which is used as a gelling agent. The aim of this research was to test the effect of CMC-Na concentrations (1%, 1.25%, and 1.5%) on the physicochemical stability of serum and to find a formulation with the best stability by testing the water content and safety. The evaluation results show that increasing the concentration of CMC-Na has an impact on increasing viscosity, pH, and adhesion, thereby providing a different gel consistency in each formula and reducing its spreadability. The best formulation is Formula-2, which is then tested for water content on respondents. The research results show that this formula has the ability to hydrate the skin, as seen from an increase in oil content of 8.39% and an increase in water content of 8.86%. Initial acute dermal toxicity test results show that the serum is safe to use on the skin and does not cause side effects or toxicity reactions.